A Observation Study of Benign Lesion of Larynx - Dr Meetha Lal Meena; Dr Ramesh Chandra Raidas; Dr Anil Kumar Garg; Dr Swagat Wagmare (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Aims and objectives: The present study was conducted to categorize the various benign appearing lesions of the larynx. Material and methods: This is a prospective study involving patient with apparently benign looking lesion not improved after two month of conservative treatment including medical treatment, avoidance of risk factors and voice therapy. 50 cases presenting with apparently looking benign laryngeal lesion were selected and subjected to micro laryngeal surgery in the Department of the Otorhinolaryngology, RNT Medical College, Udaipur (Rajasthan) Result and conclusion: Benign laryngeal lesions are prevalent in all age groups but more common between 20 to 30 years of age group. Vocal cord nodule and polyp are the most common encountered benign laryngeal lesions. Males are more affected with these lesions. Synergistic effect of vocal abuse, smoking and chronic respiratory tract infections, gastro oesophageal reflux, alcohol, atmospheric pollution and allergy, mental stress and sino nasal disease are the contributing factors for development of benign laryngeal lesions